2016
DOI: 10.1111/joa.12443
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragm degeneration and cardiac structure in mdx mouse: potential clinical implications for Duchenne muscular dystrophy

Abstract: We examined the effects of exercise on diaphragm degeneration and cardiomyopathy in dystrophin-deficient mdx mice. Mdx mice (11 months of age) were exercised (swimming) for 2 months to worsen diaphragm degeneration. Control mdx mice were kept sedentary. Morphological evaluation demonstrated increased fibrosis in the diaphragm of exercised mdx mice (33.3 ± 6.0% area of fibrosis) compared with control mdx mice (20.9 ± 1.7% area of fibrosis). Increased (26%) activity of MMP-2, a marker of fibrosis, was detected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 49 publications
3
31
0
2
Order By: Relevance
“…Utrophin, a dystrophin-like protein, participates in DGC formation, stability, and function in the absence of dystrophin [3, 4], hence utrophin upregulation remains an area of intense research interest [58]. Utrophin transcription can be driven by the exercise-sensitive PGC-1α pathway [9], however, attempts to use various exercise modalities as interventions for DMD have been met with mixed results [1013]. Direct activation of the PGC-1α pathway using transgenic and gene transfer approaches yields consistently positive results using both prevention and rescue paradigms [1418].…”
Section: Introductionmentioning
confidence: 99%
“…Utrophin, a dystrophin-like protein, participates in DGC formation, stability, and function in the absence of dystrophin [3, 4], hence utrophin upregulation remains an area of intense research interest [58]. Utrophin transcription can be driven by the exercise-sensitive PGC-1α pathway [9], however, attempts to use various exercise modalities as interventions for DMD have been met with mixed results [1013]. Direct activation of the PGC-1α pathway using transgenic and gene transfer approaches yields consistently positive results using both prevention and rescue paradigms [1418].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic volitional running was associated with decreased tension of the diaphragm in mdx mice (Selsby et al, ). More recently, Barbin et al () in swimming‐trained, 11‐month‐old mice found increased fibrosis of the diaphragm and increased activity of the fibrosis marker MMP‐2. Differently from these results, no evidence for diaphragmatic fibrosis was found after 6 weeks of low‐intensity running in our mice.…”
Section: Discussionmentioning
confidence: 95%
“…The dystrophin‐deficient mdx mouse model has been used to examine the heart–lung association in DMD. Barbin et al . demonstrated that biventricular dystrophy with pulmonary hypertension was prevalent in such mice, due in part to degeneration of the diaphragm.…”
Section: Discussionmentioning
confidence: 99%